Evaluation of clinical trial eligibility and prognostic indices in a population‐based cohort of systemic peripheral T‐cell lymphomas from the Danish Lymphoma Registry. Issue 4 (23rd July 2014) - Pedersen, Martin Bjerregaard; Hamilton‐Dutoit, Stephen Jacques; Bendix, Knud; Møller, Michael Boe; Nørgaard, Peter; Johansen, Preben; Ralfkiaer, Elisabeth; Brown, Peter De Nully; Hansen, Per Boye; Jensen, Bo Amdi; Madsen, Jakob; Schöllkopf, Claudia; et al.
Abstract: Clinical trials (CTs) are needed to improve the outcome for peripheral T‐cell lymphomas (PTCL), and accrual into CTs is one of the main recommendations in international treatment guidelines. The use of risk‐adapted strategies has been suggested as a way to optimize treatment outcome in PTCL. The aim of the present study was to evaluate CT eligibility and selected prognostic indices in a population‐based PTCL cohort of 481 PTCL patients identified from the Danish Lymphoma Registry in the period 2000–2010. According to five predefined parameters (age, performance status, P‐creatinine, P‐ALAT and measurable tumour lesion), patients were subdivided into four groups: 'younger fit', 'elderly fit', 'frail' and 'not CT eligible'. International prognostic index (IPI), prognostic index for T‐cell lymphoma (PIT) and anaplastic lymphoma kinase (ALK) protein expression were tested at subtype‐specific level. Overall, 41% of the patients were considered eligible for interventional CTs implicating curatively intended multiagent chemotherapy, including, if considered appropriate, consolidating stem cell transplantation (SCT), as part of the upfront management strategy. Moreover, 28% was elderly fit and eligible for interventional CT, including those with SCT as part of the trial design. Approximately 7% were defined as 'too frail' for aggressive treatment schedules, whereas 24% were deemed not to be eligible for any CT. Both overall and progression‐free survivals were effectively predicted by IPI and PIT ( p  <  0 . 001 ). ALK‐positive anaplastic large cell lymphoma patients were significantly younger (median age 40 vs. 62, p  <  0 . 001 ) and had a better outcome than their ALK‐negative counterparts ( p  <  0 . 001 ). However, ALK expression lost its prognostic significance when adjusting for age. In a population‐based cohort of adult Caucasian PTCL patients, approximately half were eligible for multiagent chemotherapy with or without consolidating SCT. Both IPI and PIT are useful prognostic indices in all 'primary nodal' PTCL entities. The prognostic value of ALK protein expression in anaplastic large cell lymphoma is significantly downsized when adjusting for age. Copyright © 2014 John Wiley & Sons, Ltd.